2020
DOI: 10.33503/journey.v3i1.710
|View full text |Cite
|
Sign up to set email alerts
|

Listening Difficulties Faced by the First Semester Students at Basic Listening Class

Abstract: This study aimed at describing difficulties faced by students in learning Listening. This study involved seventeen female students and eight male students taking Basic Listening course in one of private university in Malang, East Java. To gain the data, the researcher interviewed the subjects one by one. The findings, then, classified into several classes by referring to previous studies discussing listening difficulties in English as Foreign Language (EFL) classes. The findings showed that there were four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Having seen those results above, it seems all the difficulties found were similar with the previous findings found by others scholars; (Hamouda:2013, Yilmaz and Yavuz:2015, and Yahmun, Sumarti and Setyowati:2020. However, the aspect of poor equipment was not found in this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Having seen those results above, it seems all the difficulties found were similar with the previous findings found by others scholars; (Hamouda:2013, Yilmaz and Yavuz:2015, and Yahmun, Sumarti and Setyowati:2020. However, the aspect of poor equipment was not found in this study.…”
Section: Resultssupporting
confidence: 92%
“…The result revealed that the most problems faced by the students is about learning and teaching phonetics which belongs to their own strategy. Moreover, Yahmun, Sumarti and Setyowati (2020) carried out an investigation about the students' listening difficulties privat universities in Malang. Their finding showed that thelistening difficulties faced by the students are the speed and the lenght of the record.…”
Section: A Introductionmentioning
confidence: 99%
“…Students have difficulties understanding a text when speakers talk too quickly and with several accents. This result is in line with the previous studies that revealed existing difficulties faced by students concerning speed and the length of the spoken text, including vocabulary, pronunciation, and accents (Erzad, 2020;Novika et al, 2020;Yahmun et al, 2020). Consequently, they can comprehend the text during listening (Goh, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The success of learning process is determined by teacher, learning method, learning media, and learning resources, which in this study is students' worksheet based on scientific approach. All of these components must be able to support the learning process to achieve a success in the learning process (Yahmun et al, 2020).…”
Section: Abstract Article Historymentioning
confidence: 99%